2008
DOI: 10.1111/j.1365-2702.2007.02155.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of age and gender on arterial stiffness in healthy Caucasian Canadians

Abstract: Applanation tonometry, used extensively by nurses, provides early detection of central haemodynamic changes and vascular compliance at all ages. Knowledge of arterial stiffness could guide the management of primary prevention in the nursing cardiovascular risk reduction clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 20 publications
4
22
0
Order By: Relevance
“…The studies with the higher mean AIx at baseline (the current study and Noda et al) have similar standard deviations to Phillips et al and Kohler et al, suggesting that the AIx may be a more useful measure in patients with severe cardiovascular disease because the variability becomes proportionally less. Similarly, high levels of variability have been found in a healthy sample [33] and a sample comprising the offspring of patients with familial hypertension [32], but other studies reporting the AIx in a healthy population (23±1%) [34] and in young African-American and white men (0.5±2.4% and −9.0 ± 1.3%, respectively) [35] both reported far smaller standard deviations. All of these studies used the SphygmoCor equipment and software.…”
Section: Discussionmentioning
confidence: 92%
“…The studies with the higher mean AIx at baseline (the current study and Noda et al) have similar standard deviations to Phillips et al and Kohler et al, suggesting that the AIx may be a more useful measure in patients with severe cardiovascular disease because the variability becomes proportionally less. Similarly, high levels of variability have been found in a healthy sample [33] and a sample comprising the offspring of patients with familial hypertension [32], but other studies reporting the AIx in a healthy population (23±1%) [34] and in young African-American and white men (0.5±2.4% and −9.0 ± 1.3%, respectively) [35] both reported far smaller standard deviations. All of these studies used the SphygmoCor equipment and software.…”
Section: Discussionmentioning
confidence: 92%
“…A possible explanation is that in ED patients without VRFs, the occurrence of impaired arterial stiffness, at a lower grade than patients with VRFs, may be accounted for by the presence of low-grade inflammation, which has not been investigated in this study but is known to alter synthesis of structural proteins of the arterial wall, such as collagen, and therefore results in increased arterial stiffness (Hingorani et al, 2000). We are aware that increased arterial stiffness is correlated with ageing (Noon et al, 2008). However, in our population AI was higher in ED patients with and without risk factors compared with the controls with risk factors; this latter group was age-matched with that of ED patients.…”
Section: Endothelial Dysfunction and Erectile Dysfunctionmentioning
confidence: 90%
“…As Dockery and Stone (2007) suggest, the evidence may also point to increased susceptibility to air pollution due to an underlying cardiac profile that is more common among women, given that sex differences in the studies described appear more consistent with respect to cardiovascular outcomes. Some studies have shown sex differences in the cardiovascular pathways that air pollution may impact (Hoffmann et al 2009; Kublickiene and Luksha 2008; Noon et al 2008; Sztajzel et al 2008). However, the specific biological mechanisms through which PM air pollution affects all-cause mortality and cerebrovascular and CVD outcomes have not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%